2020
DOI: 10.1177/0300060520941969
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between MALAT1 rs619586 A>G polymorphism and cancer risk

Abstract: Objective This study aimed to systematically assess the effect of the metastasis associated lung adenocarcinoma transcript 1 ( MALAT1) long noncoding RNA rs619586 polymorphism on cancer risk. Methods We conducted a literature search of the PubMed, Embase, and China National Knowledge Internet databases to identify relevant studies, and calculated the pooled odds ratios (ORs) and 95% confidence intervals (CIs) for the retrieved studies using RevMan software. Results Nine eligible studies including 5968 cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To date, a number of SNPs in lncRNAs were found to be related to the development, progression, and prognosis of OSCC such as maternally expressed 3 ( MEG3 ) ( 13 ), phosphatase and tensin homolog pseudogene 1 ( PTENP1 ) ( 14 ), H19 ( 15 ), HOX transcript antisense RNA ( HOTAIR ) ( 16 ), and so on. Although MALAT1 SNPs such as rs619586 were reported to be associated with the risk or progression of several cancer types and expression of MALAT1 ( 17 ), little is known about the effects of polymorphisms of MALAT1 on the development and progression of OSCC, especially in Asian populations. In the present study, a case-control study in a Taiwanese population was performed to identify roles of MALAT1 SNPs in the risk and clinical characteristics of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of SNPs in lncRNAs were found to be related to the development, progression, and prognosis of OSCC such as maternally expressed 3 ( MEG3 ) ( 13 ), phosphatase and tensin homolog pseudogene 1 ( PTENP1 ) ( 14 ), H19 ( 15 ), HOX transcript antisense RNA ( HOTAIR ) ( 16 ), and so on. Although MALAT1 SNPs such as rs619586 were reported to be associated with the risk or progression of several cancer types and expression of MALAT1 ( 17 ), little is known about the effects of polymorphisms of MALAT1 on the development and progression of OSCC, especially in Asian populations. In the present study, a case-control study in a Taiwanese population was performed to identify roles of MALAT1 SNPs in the risk and clinical characteristics of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular etiology of CRC is still unknown, its onset is signi cantly associated with genetic variants. Single nueleotide polymorphism (SNP) is one of the most common genetic variants and involves altered cancer risk [9][10][11]. In the current study, we conducted a case-control study investigating the association between HMGA2 rs968697 polymorphism and CRC risk, and found that rs968697 C allele could reduce CRC risk compared with the T allele.…”
Section: Discussionmentioning
confidence: 95%
“…Since that overexpressed MALAT1 has been reported to be linked with a wide variety of lymphoid or solid tumors with high tumor progression and metastasis propensity and 1.5–10 fold relative upregulation based on type and stage of cancer [ 172 , 181 , 182 , 183 , 184 ]. Moreover, single nucleotide polymorphism in MALAT1, e.g., rs619586 A > G polymorphism, has also been witnessed to be linked with elevated cancer risks [ 185 ]. On the contrary, some recent studies have postulated the downregulated expression of MALAT1 in human breast and colorectal cancer, where its decreased expression is associated with lessened patient survival [ 176 , 186 ].…”
Section: Lncrnas In Female-oriented Cancersmentioning
confidence: 99%